Analysis of factors affecting the construction duration of public health emergency medical facilities - Zhao, Wenchao; He, Haibo (Frontiers in Public Health, 2023)
Objectives This study explores the factors influencing the construction duration of public health emergency medical facilities and the ways in which they can be enhanced. Methods Combining 30 relevant emergency medical facility construction cases in different cities in China from 2020 to 2021, seven condition variables and an outcome variable were selected, and necessary and sufficient condition analyses of duration influence factors were conducted using the fsQCA method. Results The consistency of seven condition variables was <0.9, which shows that the construction period of public health emergency medical facilities is not independently affected by a single condition variable but by multiple influencing factors. The solution consistency value of the path configurations was 0.905, indicating that four path configurations were sufficient for the outcome variables. The solution coverage of the four path configurations was 0.637, indicating that they covered ~63.7% of the public health emergency medical facility cases. Conclusion To reduce the construction duration, the construction of emergency medical facilities should focus on planning and design, the selection of an appropriate form of construction, the reasonable deployment of resources, and the vigorous adoption of information technology.